From chaos to a new norm: The Birmingham experience of restructuring the largest plastics department in the UK in response to the COVID-19 pandemic. Issue 12 (December 2020) - Leng, C.; Challoner, T.; Hausien, O.; Filobbos, G.; Baden, J.
Summary: The coronavirus disease 2019 (COVID-19) pandemic presented unprecedented challenges for healthcare systems worldwide. The Queen Elizabeth Hospital, Birmingham, has one of the largest burns, hands and plastics department in the UK, totalling 83 doctors. Our response to the COVID-19 response was uniquely far reaching, with our department being given responsibility of an entire 36 bed medical COVID-19 ward in addition to our commitment to specialty-specific work, and saw half of our work force re-deployed to Intensive Treatment Unit (ITU). Our aim was to exploit the high calibre of doctors found in plastic surgery, and to demonstrate, we were able to support the COVID-19 effort beyond our normal scope of practice. In order to achieve this aim, the department underwent significant structural and leadership changes. Factors considered included: rota and shift pattern changes to implement depth and resilience to sudden fluctuations in staffing levels; a preparatory phase for focussed upskilling and relevant training packages to be delivered; managing the COVID-19 ward cover and ITU deployment; adjustments to our front of house and elective specialty-specific service, including developing alternative and streamlined patient pathways; mitigating the effects on plastic surgical training during the pandemic; the importance of communications for patient care and physician wellbeing; and leadership techniques and styles we considered important. By sharing our experience during this pandemic, we hope to reflect on and share lessons learned, as well as to demonstrate that it is possible to rapidly mobilise and retrain plastic surgeons at all levels to contribute safely and productively beyond a specialty-specific scope of care.